2018
DOI: 10.1021/acs.nanolett.8b03918
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Complexes and Emerging Interlayer Electron–Phonon Coupling in BN Encapsulated Monolayer Semiconductor Alloy: WS0.6Se1.4

Abstract: Monolayer transition metal dichalcogenides (TMDs) possess superior optical properties, including the valley degree of freedom that can be accessed through the excitation light of certain helicity. While WS2 and WSe2 are known for their excellent valley polarization due to the strong spin-orbit coupling, the optical bandgap is limited by the ability to choose from only these two materials. This limitation can be overcome through the monolayer alloy semiconductor, WS2xSe2(1-x), which promises an atomically thin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Fig. 3(d)], it is known that these two Raman modes locate at 767 and 803 cm −1 , respectively, which should be Raman forbidden hBN phonons activated in WS 2 /hBN heterostructures via interlayer EPC [36,37,39]. In addition, the intensities of the Raman forbidden hBN phonons are stronger than that of the Raman active E 2g phonon at 1367 cm −1 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Fig. 3(d)], it is known that these two Raman modes locate at 767 and 803 cm −1 , respectively, which should be Raman forbidden hBN phonons activated in WS 2 /hBN heterostructures via interlayer EPC [36,37,39]. In addition, the intensities of the Raman forbidden hBN phonons are stronger than that of the Raman active E 2g phonon at 1367 cm −1 .…”
Section: Resultsmentioning
confidence: 94%
“…In principle, excitons in TMDCs would couple to exotic infrared active phonons or hyperbolic phonon polaritons in hBN, enabling another way to generate tunable hyperbolic polaritons [16,17]. Recently, interlayer exciton-phonon coupling (EPC) associated with optically silent B 1g phonons in hBN and excitons in TMDCs has been revealed in WSe 2 /hBN [36][37][38] and WS 0.6 Se 1.4 /hBN [39] heterostructures, making the optically silent hBN vibration become Raman active and giving rise to an electronic transition. However, quantum layerlayer interactions between excitons in TMDCs and infrared active phonons in hBN have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The first exploration of valley properties in alloys focused on Mo 1− x W x Se 2 at 5 K and found that there was a transition from the intrinsic valley polarization of MoSe 2 to WSe 2 as the transition metal content was varied 26 . Experiments on a WS 0.6 Se 1.4 alloy demonstrated a valley polarization of ≈31% at 14 K, which was much lower than that of both WS 2 and WSe 2 27 . A recent study of WS x Te 2− x found that the room temperature valley polarization increased from 3% in WS 2 to 37% in an unspecified alloy composition 28 .…”
mentioning
confidence: 82%
“…28 Experiments on a WS0.6Se1.4 alloy demonstrated a valley polarization of ≈31 % at 14 K, which was much lower than that of both WS2 and WSe2. 29 A recent study of WSxTe2-x found that the room temperature valley polarization increased from 3 % in WS2 to 37 % in an unspecified alloy composition. 30 The limited information regarding valley polarization in alloyed TMDs is a serious oversight as future valleytronics technologies will likely rely heavily on band engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced dimensionality leads to a notably strong Coulomb interaction between charge carriers [1]. This enhanced interaction, in turn, leads to the formation of tightly bound excitons [2][3][4][5][6], charged excitons (trions) [7][8][9][10][11], and biexcitons [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%